2019
DOI: 10.1101/587402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing virulence potential of clinical and environmental Aspergillus fumigatus isolates using Whole-genome sequencing

Abstract: 39Aspergillus fumigatus is an opportunistic airborne pathogen and the most common causative 40 agent of human fungal infections. A restricted number of virulence factors have been 41 described but none of them lead to a differentiation of the virulence level among different 42 strains. In this study, we analyzed the whole-genome sequence of a set of A. fumigatus isolates 43 from clinical and environmental origin to compare their genomes and to determine their 44 virulence profiles. For this purpose, a database… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…For example, A fumigatus strain-speci c virulence is known to be modulated by nitrogen metabolism 40 (clearly dysregulated during PCP degradation 21 ) and by the ability to thrive in low oxygen conditions 39 . The observed heterogeneity raises questions as to which genetic/epigenetic mechanisms contribute more to pathogenicity across human fungal pathogens and which are clinically relevant 53 , but to date this remains largely unknown. Our study shows that soil pollution can promote an increase in the virulence of airborne spores of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, A fumigatus strain-speci c virulence is known to be modulated by nitrogen metabolism 40 (clearly dysregulated during PCP degradation 21 ) and by the ability to thrive in low oxygen conditions 39 . The observed heterogeneity raises questions as to which genetic/epigenetic mechanisms contribute more to pathogenicity across human fungal pathogens and which are clinically relevant 53 , but to date this remains largely unknown. Our study shows that soil pollution can promote an increase in the virulence of airborne spores of Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…En esta línea, algunos autores han sugerido en estudios previos que la variabilidad intraespecie en A. fumigatus conlleva diferencias en la capacidad patogénica [7,8]. Si bien, otros como el descrito por Puértolas-Balint y col., no encuentran diferencias en virulencia entre cepas cuando se analizan aislados clínicos y ambientales de A. fumigatus [9]. estas discrepancias pueden estar relacionadas con la capacidad de formar biofilms y con la fase de desarrollo del mismo en la que se evalúa el efecto virulento.…”
Section: Efecto De La Adición De Distintas Moléculas En La Estructura...unclassified
“…In the same way, Knox et al . showed that two A. fumigatus isolates collected in the International Space Station were more lethal than the clinical reference strain in zebrafish model [ 83 ].…”
Section: Galleria Mellonella -Based Screening To Study Virulmentioning
confidence: 99%